Project-Based Learning in Building Installations in the Technical Architecture Degree Programme: Adaptando las metodologías docentes para alcanzar la excelencia en el desempeño - Zurro García, Belén; González Moreno, Sara; González Martín, José Manuel; Santamaría Vicario, Isabel; Rodríguez Saiz, Ángel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The work developed in this article shows a teaching experience based on the Active Methodology of Project-Based Learning in the Installations II subject of the Degree in Technical Architecture at the University of Burgos. To achieve excellence in the teaching and learning process, a work methodology has been designed based on the progressive development of an Execution Project through subprojects, with the aim of achieving better results in the learning process through personal performance, feedback from processes and cooperative work, all oriented to the academic and professional excellence of the students. The results obtained show that PBL is an excellent methodology for the teaching-learning process of the subject of Installations II and for the future professional performance of the students.